PURULIAR OITIJHYABAHI LOKOUTSAV TUSU/ পুরুলিয়ার ঐতিহ্যবাহী লোক উৎসব টুসু (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
The Tusu festival (also known as Tusu Parab or Makar Parab) is a harvest festival in rural Bengal. It is celebrated exclusively by unmarried women, young girls, and old alike in eastern India, which includes Purulia, Bankura, Midnapore and States of Bihar, Jharkhand and Odisha. This festival is celebrated during the winter season, typically in January, coinciding with the last day of the Poush month. It is a unifying form of common faith and belief of the agrarian society in joy of harvesting crops. The key features of the entire one month of celebrations are the Tusu songs which are the most popular traditional folk song, the food like sweets, Pitha-Puli and the famous Tusu fair. Tusu is considered as the goddess of crops. The Tusu song is sung throughout the month of Poush starting from Agrahayan Sankranti. It ends on Makar Sankranti, with the immersion of Tusu structures.             This paper, therefore, aims to explore the Rituals which perform during the Tusu Festival in Purulia as well as how it is observed in the present days. The main areas that have been highlighted in this paper are an overall idea about Tusu and how simple, hardworking rural people reflect their contemporary socio-economic, political and cultural image through Tusu songs.
Keywords: Purulia; Tusu; Tusu Gaan; Chaudal; Makar Sankranti; Tusu fair; Pitha-Puli; Folk culture